Subjective Norms Are Not Important for Millennials in Determining Their Interest in Technology: TAM and TPB Models Examines - La Pade, Alwahidin; Wahyu Prayoga, Jodi (Universitas Alma Ata, 2022)
This study examines the factors influencing the intention to use Islamic mobile banking services. In this study, factors influencing millennials' interest in using Islamic mobile banking are perceived usefulness, perceived ease of use, attitudes towards behaviour, subjective norms and behavioural control. This research is a development of previous research, which also uses a combination model of TAM (Technology Acceptance Model) and TPB (Theory of Planned Behavior). Data analysis was performed using Smart PLS Software version 3.0 and IBM SPSS 25. The results of this study indicate that perceived ease of use, perceived benefits, attitude to use, and behavioural control influence students' interest in using Islamic mobile banking. Meanwhile, subjective norms do not affect students' interest in using sharia mobile banking. The implications of this research are relevant for bank management, strategic divisions, marketing and mobile banking analysts to pay attention to the factors influencing individual interest in using mobile banking in developing their information systems.